2015
DOI: 10.2527/jas.2014-7983
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × environment interaction in individual performance and progeny tests in beef cattle

Abstract: The study reported here evaluated genotype × environment interaction in individual performance and progeny tests in beef cattle. Genetic parameters for final weight (FW), ADG, and scrotal circumference (SC) of 33,013 Nellore young bulls tested on pasture or in feedlots were analyzed. The posterior means (and highest posterior density interval with 90% of samples [HPD90]) of heritability for traits measured on pasture-raised and feedlot-raised animals were 0.44 (HPD90 = 0.40 to 0.48) and 0.50 (HPD90 = 0.43 to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
6
15
0
4
Order By: Relevance
“…Com esta metodologia, vários autores têm verificado a presença da IGA na raça Nelore, em diferentes regiões do Brasil, entre os quais se podem citar: Santana Jr. et al (2015), quanto ao ganho de peso pós-desmama, circunferência escrotal e produtividade média anual; Chiaia et al (2015), quanto ao de ganho de peso e reprodução; Raidan et al (2015), quanto ao peso final e circunferência escrotal em animais Nelore jovens; e Ribeiro et al (2015), quanto ao peso à desmana.…”
Section: Introductionunclassified
“…Com esta metodologia, vários autores têm verificado a presença da IGA na raça Nelore, em diferentes regiões do Brasil, entre os quais se podem citar: Santana Jr. et al (2015), quanto ao ganho de peso pós-desmama, circunferência escrotal e produtividade média anual; Chiaia et al (2015), quanto ao de ganho de peso e reprodução; Raidan et al (2015), quanto ao peso final e circunferência escrotal em animais Nelore jovens; e Ribeiro et al (2015), quanto ao peso à desmana.…”
Section: Introductionunclassified
“…These results are fairly consistent with the present findings. In comparison to present results, relatively less interaction effects were reported by Raidan et al (2015) for final weight with heritability values of 0.44 and 0.50, respectively for feedlot-raised and pasture-raised Nellore bulls while Espasandin et al (2011) reported similar direct heritability (0.35 and 0.34) for weaning weight in Asian J. Anim.…”
Section: Heritability For Growth Traitsmentioning
confidence: 39%
“…These authors also found that the genetic correlations between each trait expressed in an intensive fattening system and the same trait expressed in a pasture spanned from 0.31-0.93. Raidan et al (2015) reported genetic correlation to be 0.75 for final weight between Nellore cattle reared in feedlot and on pasture. On the contrary, Beffa et al (2009) found high genetic correlation estimates (0.96-1.00) for different weight traits across different management environments and Boettcher et al (2003) reported minor effects of G×E in dairy cattle with genetic correlations of 0.93 for milk yield trait.…”
Section: Estimates Of G×e For Growth Traitsmentioning
confidence: 99%
See 2 more Smart Citations